David and Zion Biblical Studies in Honor of J. J. M. Roberts - Allsopp, F.; Barré, Michael; Batto, Bernard F.; Batto, Bernard; Bouzard, Walter; Burnett, Joel; Charlesworth, James; Dick, Michael; Kselman, John; Marrs, Rick; Mettinger, Tryggve; Miller, Patrick; et al. (Penn State University Press, 2021)
J. J. M. Roberts was graduated from Harvard University, taught at The Johns Hopkins University, and then spent the bulk of his teaching career at Princeton Theological Seminary, where he influenced and was well loved by several generations of students. Here, 21 colleagues and former students contribute essays that reflect Roberts' core interests